Studi Fermentasi Biji Kopi Menggunakan Enzim Proteolitik - Imam Budiman; Farizky Wahyudi; Yunardi Yunardi; Hesti Meilina (Jurnal Serambi Engineering, 2021)
Wet fermentation by added proteolytic enzyme can be used for upgrade the taste of coffee. The enzyme was obtained from plant because of ease to get and fulfill the term of Indonesia’s constitution about halal product assurance. This study used two types of proteolytic enzyme; bromelain and zingibain that originated from pineapple and ginger, respectively. Coffee beans were fermented with weight ratio 1:4 and 3:4 (enzyme’s source: coffee beans), and compared with a non-adding control and commercial coffee. Samples were collected after 1, 2 and 3 days. Roasted beans were physical and chemical evaluated according to Indonesia National Standard (SNI-01-3542-2004). Also, the sensorial evaluation of the roasted coffee beans was determined by organoleptic test. Physical and chemical evaluation consist of water content, ash content, coffee extract, ash alkalinity and caffeine content. Sensorial evaluation includes color, aroma and flavor.